The objective assessment of contrast sensitivity function by electrophysiological means. Issue 9 (September 1984) - Howe, J W; Mitchell, K W
Abstract : In recent years it has been shown that it is of considerable clinical value to determine the visual contrast sensitivity function of the patient. This can reveal the wider effects of pathology on the visual system where visual acuity may or may not be affected. There is a comprehensive literature on subjective approaches of obtaining this function in the clinical environment but very little on alternative objective methods. This paper describes the latter approach, which exploits electrophysiological techniques using the visual evoked cortical potential (VECP) to checkerboard onset-offset stimulation. Its application in a variety of disorders of the visual system is described. The importance of selecting the most appropriate stimulus parameters is discussed, and the relative advantages and disadvantages as compared with psychophysical methods are appraised.